ESTUDIO DEL ANILLADO EN LA INDUCCIÓN FLORAL DE Persea americana MIL var. Hass EN CHAO, VIRÚ, LA LIBERTAD - Urtecho Velásquez, Gustavo Manuel (2018)
The objective of the present work was to describe the study of the ringing in the floral induction of Persea americana Mill var. Hass through the data obtained by through surveys carried out on traditional farmers in the district of Chao, province of Virú, La Libertad Region, during the months of November 2017 to February 2018. For the development of this research work, we visited different farms of avocado producers in the Chao Valley. The results show that the farmers of the hamlets of Buenavista, San Roberto, El Progreso and El Inca only perform the technique of banding 20% of the total number of farmers, which means that since it is a new technique, it will gradually be implemented. that this has as purpose to induce the floral flowering of the avocado crop which will allow a greater number of fruits with better caliber and good quality, therefore a higher production per hectare.